PROSPECTIVE RANDOMISED COMPARISON OF UNILATERAL PARAVERTEBRAL BLOCK AND SPINAL ANAESTHESIA FOR INGUINAL HERNIA REPAIR SURGERY. - Piyush, Akhil; Kumar, Rajeev; Prasad, Sudama (Student’s Journal of Health Research Africa, 2024)
Background For removal of hernia spinal anesthesia is prevalent. However, unilateral blockades with the paravertebral technique have many benefits. Objectives: This study is conducted to compare the paravertebral block and subarachnoid block as a technique of anesthesia in case of removal of an inguinal hernia Materials and Methods The patients undergoing inguinal herniorrhaphy were included in this study. They were divided into two groups. The first group was given a paravertebral block, and the second group was given a sub-arachnoid block. The vitals in both groups were compared preoperatively and throughout the surgery. The characteristics associated with anesthesia were compared statistically among the groups. Results the mean age of the Paravertebral block group was 38.67±13.27, and that of the Subarachnoid block group was 38.17±11.69 years. The mean duration of anesthesia produced in the paravertebral group was 360.34±25.6 minutes compared to the spinal anesthesia group which had a mean duration of 165.45±18.65 minutes. The time required for discharge in the paravertebral group was 195.54±25.6 minutes compared to the time required for the spinal anesthesia group which had a duration of 372.33±18.65 minutes. There were no side effects reported in the paravertebral block group. Conclusion The paravertebral unilateral blockade technique of anesthesia provides improved hemodynamic stability, decreased side effects, lesser duration of hospitalization, and optimum sensory blockade compared to spinal anesthesia. Recommendation The paravertebral blockade should be the preferred method of anesthesia for inguinal herniorrhaphy.